2017
DOI: 10.3892/ol.2017.5903
|View full text |Cite
|
Sign up to set email alerts
|

Increased methylation of human papillomavirus type 16 DNA is associated with the severity of cervical lesions in infected females from northeast China

Abstract: Abstract. Hypermethylation of the cytosine-phosphate-guanine (CpG) sites located at the 3'-major capsid protein L1 (3'L1) and the long control region (LCR) of the human papillomavirus (HPV) genome may be associated with the progression of cervical cancer (CC). However, the methylation status of the LCR of HPV type 16 DNA remains to be elucidated in an infected Chinese population. The aim of the present study was to investigate the association between methylation of the HPV 16 L1 gene and LCR, and the severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The literature search yielded 572 potentially eligible studies; 44 studies [6], [7], [8], [9],[21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60] and 8819 women were included in the analysis (supplementary table 1, supplementary figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 572 potentially eligible studies; 44 studies [6], [7], [8], [9],[21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60] and 8819 women were included in the analysis (supplementary table 1, supplementary figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that LCR methylation is more frequent in UCC than in cervical intraepithelial neoplasia (CIN). In addition, it was found that the hypermethylation of CpG islands of LCR of the PV16 increases with the severity of cervical lesions, being significantly higher in invasive cancer ( 57 ).…”
Section: Epigeneticsmentioning
confidence: 99%